PENGARUH PENYULUHAN PYMS (PEDIATRIC YORKHILL MALNUTRITION SCORE) TERHADAP PENGETAHUAN TENAGA KESEHATAN DI PUSKESMAS BIARO KABUPATEN AGAM - Ade Srywahyuni; Liza Merianti (Universitas Fort De Kock, 2021)
PYMS (Pediatric Yorkhill Malnutrition Score) is the most appropriate tool, efficient, feasible, easy to use, easy to integrate into clinical practice and requires a short time to detect nutritional status in toddlers. The purpose of this study was to determine the effect of PYMS (Paediatric Yorkhill Malnutrition Score) counseling on the knowledge of health workers at the Biaro Health Center, Agam Regency. The population in this study were health workers at the Biro Public Health Center with a total sampling of 27 health workers. This type of research uses a one group pre-test and post-test design without control. Data collection is carried out directly on the respondents by using a questionnaire. Data processing for bivariate analysis with Wilcoxon test. The results of the univariate analysis showed that before being given counseling, more than half had sufficient knowledge as many as 14 (51.9%), and after being given counseling that more than half had good knowledge were 14 (51.9%). The results of bivariate analysis with the Wilcoxon test obtained p-value 0.000 or p <0.05, thus there is an influence of knowledge on counseling. With the understanding of health workers on the use of PYMS (Pediatric Yorkhill Malnutrition Score).